Pengaruh harga dan kualitas pelayanan terhadap kepuasan pelanggan maskapai penerbangan Batik Air Banda Aceh - Yahya, Yahya -; Maulida, Zenitha -; Yusra, Yusra -; Makmur, Lidya - (Jurnal Kajian Manajemen Bisnis, 2020)
The aim of this study is to investigate the influence of price and service quality toward the customer satisfaction of Batik Air Banda Aceh. 96 respondents of this study are collected through a questionnaire. The hypothesis was tested using multiple linear regression, F-test, and t-test, to know simultaneously and partially the influence of independent variable toward the dependent variable at a 95% confidence level (Î± = 0.05). The result, based on the t-test and partial test, shows that price and service quality influence the customer satisfaction level of Batik Air in Banda Aceh. Implication and suggestion also discussed in this study.